Persistent Left Unilateral Apraxia and a Disconnection Theory - Atsushi Yamadori; Yukio Osumi; Toru Imamura; Yoko Mitani (Behavioural Neurology)
A case of persistent left unilateral apraxia caused by a post-traumatic callosal lesion is reported. Based on an analysis of the nature of the motor disturbances it is concluded that the disconnection is neither for linguistic nor mnemonic information about praxis but motor control information which is activated through conscious intention.